Fluorescent probes for the imaging of lipid droplets in live cells - Tian, He; Sedgwick, Adam C.; Han, Hai-Hao; Sen, Sajal; Chen, Guo-Rong; Zang, Yi; Sessler, Jonathan L.; James, Tony D.; Li, Jia; He, Xiao-Peng (Coordination chemistry reviews, 2021)
•The biological importance of lipid droplets (LDs).•Brief introduction to the formation and physiological functions of LDs.•Recent examples of LD-based fluorescent probes.•The various fluorescence mechanisms exploited to create LD probes. Lipid droplets (LDs) are cellular organelles that are essential for maintaining lipid and energy homeostasis. Once regarded as merely inert fat particles, they are now recognized as highly dynamic, mobile organelles required for preventing lipotoxicity and for interacting and cooperating with various organelles. Despite the progress made in understanding the role of LDs, a number of fundamental questions remain unanswered. Effective imaging agents for observing the morphology and dynamic physiological processes of LDs in cells could help address this knowledge gap. Such probes are expected to aid in our understanding of LDs and facilitate the development of new and effective therapeutics. In this review, we have provided a brief introduction to the formation and physiological functions of LDs in an attempt to highlight the importance of these underappreciated organelles. Recent examples of LD-based fluorescent probes are discussed, including the fluorescence phenomenon used in their design. To date, both intramolecular charge transfer (ICT) and aggregation-induced emission (AIE) fluorescence mechanisms have been exploited to create LD probes. However, alternative strategies can be envisioned. We hope the readers will be enlightened as to the importance of these key organelles, will be poised to exploit existing probes to explore various biological applications, and be inspired to create new LD fluorescent sensors that will further our understanding of LDs and their associated physiology.